Analisis Hubungan Kemiskinan, Angka Melek Huruf Dan PDRB Terhadap Ketimpangan Pendapatan di Provinsi Sumatera Utara - Harbain Harbain; Muhammad Harfandi Harahap; Restu A Suryaman (Management And Business Progress, 2025)
Income inequality is a crucial issue in sustainable economic development. This study aims to analyze the relationship between poverty rates, literacy rates, and Gross Regional Domestic Product (GRDP) and income inequality in North Sumatra Province during the 2012–2024 period. The data used are secondary data obtained from the Central Statistics Agency (BPS) of North Sumatra Province and the Central Statistics Agency (BPS) of Indonesia. The analytical method used is multiple linear regression with the Ordinary Least Squares (OLS) approach. The results of the study show that partially, only the literacy rate has a negative and significant effect on income inequality (t = -2.778; sig = 0.021) because t count = -2.778 > from t table (1.833) and significant sig = 0.021 < 0.05, while poverty has a positive and insignificant effect (t = 1.463; sig = 0.177) and GRDP has a negative but insignificant effect (t = -0.455; sig = 0.660). Simultaneously, the variables of poverty, GRDP, and literacy rate have a significant effect on income inequality (F count = 7.855; sig = 0.007). The coefficient of determination (R²) value of 0.724 indicates that 72.4% of the variation in income inequality is explained by these three variables. The results of this study indicate that income inequality in North Sumatra Province can be reduced by improving the quality of education (through increasing literacy rates). Future economic development policies should emphasize equitable access to education across the province.